Pelvic-peritoneal tuberculosis mimicking ovarian cancer with elevated CA 125 - García, F. (2015)
From the year 1000. C. tuberculosis known as a clinical entity. However, it was not until 1744 when Morgagni described the first case of genital condition in a necropsy of a 20-year-old who died from the disease and who cheesy material in the uterus and fallopian tubes are found.